System analysis of the extrusion process to determine the objectives and structure of the control system - Ярощук, Людмила Дем’янівна; Жученко, Олексій Анатолійович (Eastern-European Journal of Enterprise Technologies, 2013)
The article is devoted to the system analysis of the extrusion of polymeric materials in order to determine the objectives and structure of a control system. The algorithm of the system analysis of technological objects of different complexity was suggested on the example of the extrusion process. The algorithm provides the definition of the tasks that are formulated for the production system as a whole: productivity and product quality, economic effectiveness, social and environmental tasks. A detailed analysis of the separate hardware components of the extrusion was carried out and conclusions were drawn regarding the tasks and modes of their operation. The block diagrams of control problems and ways of their solutions were developed for the heating, start-up and normal modes of operation of the extruder. The results provide the conclusions concerning the improvement of the process due to the synthesis of an adaptive control system with elements of artificial intelligence. Such a system will reduce energy costs and improve the quality of the finished product